Corrigendum to “Exosomes improved the in vitro anti-melanoma efficacy of dihydroartemisinin” [J. Drug Delivery Sci. Tech. 9 (2024) 105957] (Journal of Drug Delivery Science and Technology (2024) 99, (S1773224724006269), (10.1016/j.jddst.2024.105957)) - Kumar D.N.; Chaudhuri A.; Dehari D.; Gamper A.M.; Kumar D.; Agrawal A.K. (My University, 2025)
The authors regret that unfortunately, we provided the duplicate SEM images in Fig. 1 image in our recently published article. Now we want to replace Fig. 1 image with the below given image.[Formula presented] The authors would like to apologise for any inconvenience caused. © 2024